Spatio-temporal distribution of pufferfish (Tetraodontidae) along the Turkish coast of the Mediterranean Sea - MUTLU, ERHAN; DE MEO, ILARIA; MIGLIETTA, CLAUDIA (Mediterranean Marine Science, 2021)
Pufferfish represent a serious threat to the marine ecosystem in the Mediterranean Sea. To better understand the population dynamics of pufferfish and their relation with ecological parameters, six pufferfish species were studied in two fishing and one non-fishing zone in one of the most oligotrophic regions of the Mediterranean Sea during 2014 and 2015, including different habitats of vegetated and non-vegetated and seasons. The results provide information on pufferfish ecological status compared with more eutrophic zones in which these species could potentially worsen their impact. Four species were common in the study area and two were rare. The dominant species was Lagocephalus suezensis, reaching abundances of 11,000 ind/km2 at 25 m in October, followed by Lagocephalus sceleratus, Lagocephalus guentheri, and Torquigener flavimaculosus. The rarest species, Tylerius spinosissimus and Sphoeroides pachygaster, reached higher abundance and biomass in October and February than the other sampling months. The riverine and meadow habitats played a crucial role for nursing and reproduction in the population dynamics of Lagocephalus species, while T. flavimaculosus was absent in these areas. Sex ratios changed depending on season and location. The occurrence of larger individuals of Lagocephalus spp. and T. flavimaculosus at greater depths evidenced an ontogenetic migration. Overall, length-weight (L-W) relationships indicate isometric growth for each of the species studied. Pufferfish populations were primarily a function of habitat and depth of seafloor and secondarily with water productivity.